PERFECTED enhanced recovery pathway (PERFECT-ER) versus standard acute hospital care for people after hip fracture surgery who have cognitive impairment: a feasibility cluster randomised controlled trial. Issue 2 (28th February 2022) - Cross, Jane L; Hammond, Simon P; Shepstone, Lee; Poland, Fiona; Henderson, Catherine; Backhouse, Tamara; Penhale, Bridget; Donell, Simon; Knapp, Martin; Lewins, Douglas; MacLullich, Alasdair; Patel, Martyn; et al.
Abstract : Objectives: Assess feasibility of a cluster randomised controlled trial (RCT) to measure clinical and cost-effectiveness of an enhanced recovery pathway for people with hip fracture and cognitive impairment (CI). Design: Feasibility trial undertaken between 2016 and 2018. Setting: Eleven acute hospitals from three UK regions. Participants: 284 participants (208 female:69 male). Inclusion criteria: aged >60 years, confirmed proximal hip fracture requiring surgical fixation and CI; preoperative AMTS ≤8 in England or a 4AT score ≥1 in Scotland; minimum of 5 days on study ward; a 'suitable informant' able to provide proxy measures, recruited within 7 days of hip fracture surgery. Exclusion criteria: no hip surgery; not expected to survive beyond 4 weeks; already enrolled in a clinical trial. Intervention: PERFECT-ER, an enhanced recovery pathway with 15 quality targets supported by a checklist and manual, a service improvement lead a process lead and implemented using a plan–do–study–act model. Primary and secondary outcome measures: Feasibility outcomes: recruitment and attrition, intervention acceptability, completion of participant reported outcome measures, preliminary estimates of potential effectiveness using mortality, EQ-5D-5L, economic and clinical outcome scores. Results: 282 participants were consented and recruited (132, intervention) from a target of 400. Mean recruitment rates were the same in intervention and control sites, (range: 1.2 and 2.7 participants/month). Retention was 230 (86%) at 1 month and 54%(144) at 6 months. At 3 months a relatively small effect (one quarter of an SD) was observed on health-related quality of life of the patient measured with EQ-5D-5L proxy in the intervention group. Conclusion: This trial design was feasible with modifications to recruitment. Mechanisms for delivering consistency in the PERFECT-ER intervention and participant retention need to be addressed. However, an RCT may be a suboptimal research design to evaluate this intervention due to the complexity of caring for people with CI after hip fracture. Trial registration number: ISRCTN99336264 .